Students’ Responses to a Scavenger Hunt for First Year Engineering Orientation - Lindsay, Euan; Gray, S.; Lloyd, Natalie (Unable to source information, 2012)
Orientation is an essential part of the transition into engineering studies at University. A successful orientation introduces students to their department and to university studies, providing important information and assisting the students in making friends and acclimatising to the university lifestyle. The university of XXXX has trialled the OrientHunt - a scavenger hunt intended to deliver information to students through the active learning environment of a campus-wide roaming team-based activity. This paper details the outcomes of the first implementation of the OrientHunt. It provides a report of the students’ exit survey responses. The students believe the scavenger hunt was successful in its objectives of preparing them for transition as well as providing social opportunities for meeting other students; they also felt that a range of communication and teamwork skills had been improved by the experience.